1p36 Deletion Syndrome and Left Ventricular Non-compaction Cardiomyopathy—Two Cases Report - Jang, Subin; Taber, Allison; Bateman, Michael G.; Steiner, Marie E.; Ameduri, Rebecca K.; Griselli, Massimo (Frontiers in Pediatrics, 2021)
1p36 deletion is the most common terminal deletion syndrome in humans. Herein, we report two cases, a 5-month-old female and a 14.5-year-old female, both with 1p36 deletion and left ventricular non-compaction cardiomyopathy. They presented with severely depressed left ventricle function and underwent heart transplantation with excellent outcomes. Given the incidence of heart defects and cardiomyopathy in 1p36 deletion syndrome, it should be recommended that children with this genetic condition have screening for cardiac disease. These cases add to the literature by demonstrating the potential therapeutic options for non-compaction in 1p36 deletion syndrome and show that the outcomes are comparable to children who do not have this genetic condition.